PENATALAKSANAAN REMAJA 16 TAHUN DENGAN BABY BLUES SYNDROME DENGAN PENDEKATAN KEDOKTERAN KELUARGA - Totalia, Lely Sustantine; Susanto, Tirta D; Soeryani, R. Wianti (CV. Jasa Sukses Abadi, 2024)
Adolescents are an age group that is vulnerable to various changes, both physically and psychologically. Adolescence is characterized by various challenges, including in terms of mental readiness to face new roles, such as becoming a mother. These conditions can trigger the onset of baby blues symptoms, such as feelings of sadness, anxiety, and excessive fatigue after childbirth.This case describes the treatment of a 16-year-old adolescent girl who experienced baby blues after giving birth to her first child with a family medicine approach. The patient complained of feelings of sadness, moodiness, difficulty sleeping, often brooding and crying without cause, and feeling useless and unsuitable for motherhood. The patient also showed symptoms such as not wanting to take care of the child, including breastfeeding, and sometimes even wanting to hurt the child because of fatigue. This condition was exacerbated by limited social support, where the husband's parents and the patient's parents were in a distant city. Through a holistic and comprehensive family medicine approach, the medical team sought to identify the factors contributing to the emergence of baby blues in the patient, as well as evaluate the effectiveness of the interventions made to help the patient overcome her condition. This case report is expected to serve as a reference for health practitioners in dealing with similar cases in the future and increase public awareness, especially among adolescents, regarding the importance of paying attention to mental health. Interventions involving medical, psychological and social support have been shown to be effective in helping patients overcome challenges and adapt to their new role as mothers.